2021
DOI: 10.1093/jn/nxab066
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Multiple Micronutrient Powder Point-of-Use Fortification Trial Implemented in Indian Preschools Increases Expressive Language and Reduces Anemia and Iron Deficiency

Abstract: Background Anemia is a global public health problem that undermines childhood development. India provides government-sponsored integrated nutrition/child development preschools. Objectives This double-masked, cluster-randomized controlled trial examines whether point-of-use multiple micronutrient powder (MNP) compared with placebo fortification of preschool meals impacts child development and whether effects vary by preschool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 57 publications
2
25
1
Order By: Relevance
“…Table 2 summarizes the characteristics of RCTs contained in this review. In summary, 50% of trials were conducted in developed countries [55][56][57][58][59][60] and 50% in low and middleincome countries (LMICs) [61][62][63][64][65][66]. Four experimental studies were conducted in rural areas with low socioeconomic status [61,62,64,66], and six studies in urban areas with high socioeconomic status [55][56][57][58][59][60].…”
Section: Description Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 summarizes the characteristics of RCTs contained in this review. In summary, 50% of trials were conducted in developed countries [55][56][57][58][59][60] and 50% in low and middleincome countries (LMICs) [61][62][63][64][65][66]. Four experimental studies were conducted in rural areas with low socioeconomic status [61,62,64,66], and six studies in urban areas with high socioeconomic status [55][56][57][58][59][60].…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Four experimental studies were conducted in rural areas with low socioeconomic status [61,62,64,66], and six studies in urban areas with high socioeconomic status [55][56][57][58][59][60]. The earliest trial was completed in 2004 [58] and the latest in 2020 [65]. The shortest intervention was implemented for two months [58], and the longest trial lasted ten months [61].…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] Efficacy trials in LMICs have shown that MNP can deliver sufficient iron to reduce anemia and the prevalence of iron deficiency in young children 14 and may also increase cognitive performance. 15 While MNP is efficacious when compliance is ensured, adherence to MNP protocols among beneficiaries varies widely. 16 MNP has been promoted as a low-cost and effective intervention, 12 reportedly costing $3.60 per child per year, 17 with a cost-effectiveness ratio as high as 37:1 (calculated as the present value of the gain in earnings for each dollar spent on the intervention).…”
Section: Introductionmentioning
confidence: 99%
“…11 , 12 , 13 Efficacy trials in LMICs have shown that MNP can deliver sufficient iron to reduce anemia and the prevalence of iron deficiency in young children 14 and may also increase cognitive performance. 15 While MNP is efficacious when compliance is ensured, adherence to MNP protocols among beneficiaries varies widely. 16 …”
Section: Introductionmentioning
confidence: 99%